Factors influencing the psychological independence of retired community-dwelling older adults in Japan - Hirano, Yuko O.; Tamagawa, Ranze; Matsumoto, Takako (Frontiers in Psychology, 2022)
Background: In an aging society, it is necessary to promote successful aging by helping older adults maintain engagement in social activities, especially after retirement. To help older adults maintain psychological independence, they must learn to let go of corporate attachments and increase social participation in their community after retirement. However, shifting one’s mindset from the workplace to the local community can be difficult, especially for Japanese people who prioritize work over local community activities. Few studies have investigated the factors associated with the psychological independence of community-dwelling older adults, so this study aimed to identify factors that influence the psychological independence of older adults in T town, a typical commuter town in Japan. Methods: A self-administered, anonymous questionnaire was distributed to 246 neighborhood association members aged 65 and older. T-test, Pearson’s correlation coefficient, Cronbach’s alpha, and multiple regression analysis were used to develop a model to predict psychological independence and two subconstructs, purposefulness and personal accountability. Results: The results demonstrated that psychological independence, purposefulness, and personal accountability were significantly predicted by having abilities that are useful to other people (β = .399, p = .001; β = .277, p = .019; and β = .394, p = .001, respectively). Conclusion: The findings of this study suggest that older adults can maintain psychological independence using their existing characteristics, such as those that are useful to others in the community.